The Influence of Educational Service Quality on Student Satisfaction: A Study on the Anti-Corruption Cultural Education Course (PBAK) in the Midwifery Department of Poltekkes Kemenkes Jakarta I - Payung Hasibuan; Jusuf Kristianto; Feryanda Utami; Adelina Barus (Syntax Corporation Indonesia, 2023)
Background: Educational services are one of the intangible services. One important factor for the success of students in pursuing higher education is the quality of education services in the Teaching and Learning Process (PBM) that are good and meet student expectations. Objective: This study aims to determine whether there is a significant influence of the quality factors of educational services, specifically in the course of Anti-Corruption Cultural Education (PBAK), on overall student satisfaction, as well as to identify the dominant factors of educational service quality that influence student satisfaction at Poltekkes Kemenkes Jakarta I. Research Methodology: The population of this study consists of all students in the Midwifery department. The research sample was taken using a purposive sampling method, with a total of 58 students from 1A and 1B levels. The data collection technique used was a questionnaire. Prior to using the questionnaire, the researcher conducted validity and reliability tests. Instrument validity was assessed through factor analysis and item score analysis with total scores. Regression analysis was employed to determine the dominant factors of service quality that influence student satisfaction in the PBAK course in the Midwifery Department, Poltekkes Kemenkes Jakarta I. Research Findings: Based on the ANOVA or F-test results, the obtained F-value was 92.077 with a significance level of 0.000. This indicates that the independent variables (Tangible, Reliability, Responsiveness, Confidence, and Empathy) collectively influence the dependent variable (Student Satisfaction). The Backward method testing also reveals that Appearance (Tangible) and Responsiveness (Responsiveness) variables are dominant factors influencing Customer Satisfaction. Conclusion: Student satisfaction with the performance of lecturers in the implementation of the PBAK course in the Midwifery Department, Poltekkes Kemenkes Jakarta I, is influenced by the Tangible and Responsiveness factors of the lecturers.